Within player monitoring of wellness, sleep and readiness to play and the effect of training load in elite football - Spencer, M.; Wiig, H.; Andersen, T. E.; Ingebrigtsen, J.; Luteberget, L. S. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Frequent matches and training sessions in elite football result in high training loads and constrained time for recovery. Careful planning of training loads, using valid and reliable tools, may assist to reduce injury risk and increase physical performance [1]. Monitoring individual training load, perception of wellness and sleep may be useful tools for tracking training load and the response to training and matches, and therefore improve training preparations. An important question is therefore how training load is related to wellness, sleep and readiness to play. Therefore, the aim of this study was to assess how wellness, sleep, readiness to play vary in the days pre- and post-match over two consecutive seasons within one elite football team.